THE MODERATING EFFECT OF CORPORATE GOVERNANCE STRENGTH ON THE RELATIONSHIP BETWEEN FAIR VALUE REPORTING AND STOCK RETURN VOLATILITY - Yuyun Yuniarti Layn; Amiruddin Amiruddin; Dharmawati Dharmawati (CV. Adiba Aisha Amira, 2026)
This study aims to explore the relationship between fair value reporting and stock return volatility, and to assess the role of strengthened corporate governance as a moderating variable. Fair value reporting has become an important topic in the accounting and finance literature due to its ability to provide more relevant information regarding the value of a company's assets and liabilities, but at the same time, it increases uncertainty related to market fluctuations. The strength of corporate governance is believed to influence the extent to which fair value information impacts investor behavior and stock price volatility. This study uses a literature review method, examining various articles, journals, and empirical studies related to fair value reporting, corporate governance, and stock volatility. The literature analysis indicates that companies with stronger governance tend to be able to reduce the uncertainty created by fair value reporting, thus more controlling stock return volatility. These findings provide a theoretical understanding of the moderating mechanism of corporate governance in the context of fair value disclosure and its implications for the capital market, and open opportunities for further empirical research to quantitatively test this relationship.